Global survey of escape from X inactivation by RNA-sequencing in mouse - Yang, Fan; Babak, Tomas; Shendure, Jay; Disteche, Christine M. (Genome Research, 2010)
X inactivation equalizes the dosage of gene expression between the sexes, but some genes escape silencing and are thus expressed from both alleles in females. To survey X inactivation and escape in mouse, we performed RNA sequencing in Mus musculus × Mus spretus cells with complete skewing of X inactivation, relying on expression of single nucleotide polymorphisms to discriminate allelic origin. Thirteen of 393 (3.3%) mouse genes had significant expression from the inactive X, including eight novel escape genes. We estimate that mice have significantly fewer escape genes compared with humans. Furthermore, escape genes did not cluster in mouse, unlike the large escape domains in human, suggesting that expression is controlled at the level of individual genes. Our findings are consistent with the striking differences in phenotypes between female mice and women with a single X chromosome—a near normal phenotype in mice versus Turner syndrome and multiple abnormalities in humans. We found that escape genes are marked by the absence of trimethylation at lysine 27 of histone H3, a chromatin modification associated with genes subject to X inactivation. Furthermore, this epigenetic mark is developmentally regulated for some mouse genes.